PELATIHAN DIGITAL MARKETING SEBAGAI UPAYA PENINGKATAN JANGKAUAN PEMASARAN PADA UKM SEKAR SARI MANDIRI SLEMAN - Atika Hatta Hambali; Bianka Andriyani; Y. Yohakim Marwanta (Prestise: Jurnal Pengabdian Kepada Masyarakat Bidang Ekonomi dan Bisnis, 2025)
Digital marketing represents an essential digital capability that entrepreneurs, including micro, small, and medium enterprises (MSMEs), are required to develop in response to increasing market digitalization. This marketing strategy utilizes digital platforms to promote products to the general public. This community service program aims to provideunderstanding and training related to digital marketing to the Sekar Sari Mandiri MSME in Turi, Sleman, and to develop a marketing website with partners to expand their marketing reach. The training teaches the use of digital marketing in managing marketing through platforms such as Instagram, TikTok, Facebook, and WhatsApp. This training uses creativeapplications such as Canva, CapCut, and ChatGpt to support the effectiveness and efficiency of marketing planning. This community service method uses a participatory approach, placing the community as active subjects in every stage, from planning to evaluation. The results of the community service program show that partners who were initially unable to conduct digital marketing are now able to create marketing content and conduct marketing through the website. This includes filling in product descriptions with attractive product photos and operating the website developed with the community service team.